Private international law’s ambivalent humanism - Banu, R (University of Toronto Press, 2024)
Karen Knop’s fresh reading of James Lorimer’s The Institutes of the Law of Nations (1883) recovered the image of what she termed ‘the private citizens of the world.’ She introduced this figure from Lorimer’s forays into private international law in order to investigate to what extent the attributes of private citizens of the world are restored or refracted through public international law doctrines and theories. But how should private international law re-engage with the private citizens of the world? I caution that, by reference to this familiar figure, one may too easily ascribe either an inherent humanism or an inherent agnosticism to private international law. Neither would be in line with Karen’s critical project. By contrast, I suggest that Karen’s revival of the private citizens of the world should prompt private international law scholars to look carefully into their field’s past and present and reckon with the field’s more ambivalent humanism. This article travels past Lorimer’s writings into the inter-war period to reveal the fragility of sustaining the private citizens of the world via private international law in Europe, Latin America, and the British Empire. It suggests that those historical puzzles at the root of private international law’s ambivalent humanism continue to this day.